ХОРИЖ МАКТАБЛАРИ ЎҚИТУВЧИЛАРИНИНГ БИЛВОСИТА МАЛАКА ОШИРИШ КУРСЛАРИ БЎЙИЧА ҚАРАШЛАРИ - Mallayeva, Ozoda (Журнал иностранных языков и лингвистики, 2021)
Analyzing foreign experience in this area, we see that in most developed countries today, the form of direct professional development (training in educational programs) is not a priority in the field of professional development of teachers, but rather indirect forms of professional development. We will focus on indirect forms of foreign experience in improving the skills of teachers.